PERAN FIRM SIZE DALAM MEMODERASI DETERMINAN CASH HOLDING - Sophia , Natasya Yohana; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study was to analyze the effect of profitability, liquidity, and net working capital on cash holding moderated by firm size. This study uses data on property and real estate sector companies listed on the IDX. This study used 44 company samples with 132 observations that met the purposive sampling criteria. The data used is secondary data from the company's financial statements. The data processing technique used uses moderation regression analysis with the help of Microsoft Excel 2016 and E-views 12. The results obtained from this study are liquidity has a negative effect on cash holding, while profitability and net working capital do not have an effect on cash holding. Firm size cannot moderate the effect of profitability and net working capital on cash holding, while firm size can moderate the effect of liquidity on cash holding.